A techno-economical evaluation for installation of suitable wind energy plants in western Marmara, Turkey - Goekcek, Murat; Erdem, Hasan Hueseyin; Bayuelken, Ahmet (SAGE PUBLICATIONS INC, 2007)
The increasing environmental concerns in recent years about global warming and the harmful effects of carbon emissions have created a new demand for clean and sustainable energy sources, such as wind, solar etc. Turkey has important wind energy potential especially in the Marmara region, coasts of western and southern Anatolia. However, utilization of this potential is still below the desired level. In this study, wind energy potential of Kirklareli province in the northwestern Marmara region of Turkey was analyzed. Economical evaluation of the wind energy in the site was made by using the levelised cost method. The energy production was determined by means of the time-series and Weibull approaches. The selected turbines for investigation are of various rated powers ranging from 300 kW to 2500 kW. The effect of hub height on the energy production was investigated for various hub heights. The results showed that the cost of energy production per kWh for the related site vary between 5.37 and 11.91. An increase in the escalation rate of the operating and maintenance cost from 0 to 10%, increases the unit energy cost about 6%. For the wind turbine of 2300 kW rated power, as the hub height increases from 80 to 100 m, the cost of energy decreases about 4%.
Keywords: wind energy production; energy cost; wind power; western Marmara; Turkey; RESOURCE ASSESSMENT; CAPACITY FACTOR; SPEED; IZMIR; Energy & Fuels